MENDORONG LOYALITAS PELANGGAN MELALUI CUSTOMER ENGAGEMENT DAN BRAND EXPERIENCE PADA KEDAI KOPI DI MATARAM - Amiruddin Kalbuadi; Lale Puspita Kembang; Agus Hermanto; Lalu Ahmad Murdhani (Taksasila Edukasi Insani, 2026)
This study aims to examine the effect of customer engagement and brand experience on customer loyalty at coffee shops in Mataram City. A quantitative causal-explanatory approach was employed. The population comprised all coffee shop consumers in Mataram, with an infinite population size. A sample of 385 respondents was selected using purposive sampling, with criteria including age ≥17 years, minimum three visits per month. Data were collected through questionnaires using a 5-point Likert scale, distributed both directly and via Google Forms. Data analysis was performed using descriptive statistics and Partial Least Squares (PLS) with SmartPLS 4.0, including outer model evaluation (convergent validity, discriminant validity, reliability) and inner model evaluation (R-square, Q-square, hypothesis testing via bootstrapping). The results indicate that customer engagement has a positive and significant partial effect on customer loyalty (β=0.286; t=4.872; p=0.000). Brand experience also has a positive and significant partial effect, with a more dominant influence (β=0.452; t=8.122; p=0.000). Simultaneously, customer engagement and brand experience significantly affect customer loyalty (β=0.677; t=6.330; p=0.000), with an R-square value of 0.538, meaning both variables explain 53.8% of customer loyalty variation.Keywords : Brand Experience, Coffee Shop, Customer Engagement, Customer Loyalty, Mataram